Role performance of community health volunteers and its associated factors in Kuching district, Sarawak - Hsien, Melvin Liang Chung; Helmy, Hazmi; Whye, Lian Cheah (Hindawi Publishing Corporation, 2017)
The objective of this study was to assess the role performance among KOSPEN community health volunteer in Kuching district and its associated factors. This was a cross-sectional study, conducted in 21 localities in Kuching with a total of 210 respondents. Data were collected using validated interviewer-administered questionnaires and analyzed using SPSS version 22.0. The respondents comprised 55.2% females, 81.9% married, and 41.4% aged above 45 and above and 72.4% completed their education up to secondary school. The result revealed that 59.0% of the respondents agreed and understood their role performances. Multiple Logistics analysis revealed that factors associated with role performance were age group (p=0.003), education level (p<0.001), marital status (p=0.025), prestige and respect (p=0.012), being seen as "doctor" in community (p=0.003), job aids (p=0.009), training location (p=0.001), and supervision by community (p<0.001). To increase and maintain the work performance of CHVs, commitment from the government, policy makers, stakeholders, and the communities is required.